Concomitant Ankle Injuries Associated With Tibial Shaft Fractures. (October 2015) - Jung, Ki Jin; Chung, Chin Youb; Park, Moon Seok; Chung, Myung Ki; Lee, Dong Yeon; Koo, Seungbum; Lee, Kyoung Min
Background: Ankle injuries associated with tibial shaft fractures can cause postoperative ankle pain and stiffness even when satisfactory bony union has been achieved. Although several previous studies have described these injuries, they have not been clearly defined or classified in terms of ankle injury type or need for surgical fixation. Methods: Seventy-one consecutive patients (mean ± SD age, 48.3 ± 16.7 years; 37 men and 34 women) with tibial shaft fractures who underwent computed tomography examination were included. Data were collected including age, sex, body mass index, fracture location of the tibia and fibula (in percentile of length), tibial fracture shape (spiral, oblique, transverse), presence and pattern of concomitant ankle injuries (on the distal tibial articular surface), and necessity for surgical fixation of ankle injuries. Factors associated with concomitant ankle injuries associated with tibial shaft fractures were analyzed by logistic regression analysis. Results: A total of 47 (64.7%) of the 71 tibial shaft fractures involved concomitant ankle injuries, including 8 cases of combined lateral malleolar fracture, posterior malleolar fracture, and anterior inferior tibiofibular ligament (AITFL) avulsion fracture; 9 cases of combined posterior malleolar fracture and AITFL avulsion fracture; 6 cases of combined lateral malleolar fracture and posterior malleolar fracture; 1 case of combined lateral malleolar fracture and AITFL avulsion fracture; 10 cases of posterior malleolar fracture; 7 cases of lateral malleolar fracture; 5 cases of AITFL avulsion fracture; and 1 unclassified fracture. Of these, 34 of the ankle injuries required surgical fixation. Spiral-type tibial shaft fracture was significantly associated with concomitant ankle injury ( P = .001). Conclusions: Orthopaedic surgeons should be aware that tibial shaft fractures, especially spiral-type fractures, are frequently associated with ankle injuries, such as lateral malleolar fractures, posterior malleolar fractures, and AITFL avulsion fractures. A considerable portion of these cases may necessitate surgical fixation. We recommend all spiral-type tibial shaft fractures routinely undergo computed tomography examination. Level of Evidence: Level III, comparative series.